A Survey of Challenges Experienced by New Learners Coding the Rorschach. Issue 3 (4th May 2017) - Viglione, Donald J.; Meyer, Gregory J.; Resende, Ana Cristina; Pignolo, Claudia
ABSTRACT: Learning to code the imagery, communication, and behavior associated with Rorschach responding is challenging. Although there is some survey research on graduate students' impressions of their Rorschach training, research has not identified which coding decisions students find to be the most problematic and time-consuming. We surveyed students to identify what they struggled with most when learning coding and to quantify how difficult it is to learn how to code. Participants ( n = 191) from the United States, Brazil, Denmark, Israel, and Italy rated 57 aspects of coding using a 4-point scale that encompassed both the time required to code and the subjective difficulty of doing so. Mean ratings for coding in general indicated that students considered the overall task challenging. Ratings also revealed that students struggled most with Cognitive Special Scores, Determinants, and extrapolating from the tables to code Form Quality for objects that were not specifically listed. The findings offer suggestions about how to improve the guidelines for some of the more difficult variables and where it is most necessary to focus teaching time. Taking these steps might help new students in learning the Rorschach.